2008
DOI: 10.1073/pnas.0804821105
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 promotes survival through translational control of Mcl-1

Abstract: Activation of the phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway is a frequent occurrence in human cancers and a major promoter of chemotherapeutic resistance. Inhibition of one downstream target in this pathway, mTORC1, has shown potential to improve chemosensitivity. However, the mechanisms and genetic modifications that confer sensitivity to mTORC1 inhibitors remain unclear. Here, we demonstrate that loss of TSC2 in the E-myc murine lymphoma model leads to mTORC1 activation and accelerated oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
256
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(268 citation statements)
references
References 28 publications
11
256
1
Order By: Relevance
“…Mcl-1 can counteract some of the pro-apoptotic events induced by c-Myc in the Em-Myc mice and result in lymphomas. 161,163,164 As mentioned before the Rheb GTPase is an activator of mTORC1. Rheb is highly expressed in some human lymphomas 31,[165][166][167] and other cancers.…”
Section: Tsc2/rheb/mtorc1 Translation Initiation/elongation and Leukemiamentioning
confidence: 80%
See 1 more Smart Citation
“…Mcl-1 can counteract some of the pro-apoptotic events induced by c-Myc in the Em-Myc mice and result in lymphomas. 161,163,164 As mentioned before the Rheb GTPase is an activator of mTORC1. Rheb is highly expressed in some human lymphomas 31,[165][166][167] and other cancers.…”
Section: Tsc2/rheb/mtorc1 Translation Initiation/elongation and Leukemiamentioning
confidence: 80%
“…One of the deregulated targets in the TSC2-(loss of heterozygosity)/Em-Myc lymphomas is Mcl-1 (ref. 164). Mcl-1 expression is induced and the mRNAs encoding Mcl-1 are translated by the increased activity of the mTORC1-eIF4E complex.…”
Section: Tsc2/rheb/mtorc1 Translation Initiation/elongation and Leukemiamentioning
confidence: 99%
“…In addition, mTORC1 induces oxidative phosphorylation by facilitating YY1/PGC1α complex formation (Cunningham et al , 2007) and supports aerobic glycolysis (Duvel et al , 2010). In the Eμ‐Myc mouse model, mTORC1 activation was shown to accelerate lymphomagenesis by inhibiting Myc‐induced apoptosis through translational upregulation of the anti‐apoptotic protein myeloid cell leukemia 1 (Mcl1; Mills et al , 2008), suggesting a collaboration of Myc and mTORC1 in tumor initiation. On the contrary, MYC amplification was shown to confer resistance to mTORC1 inhibition through transcriptional activation of the eukaryotic translation initiation factor 4E (eIF4E), suggesting that mTORC1 function is not critical in the context of high MYC expression (Ilic et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It would therefore be interesting to investigate those proapoptotic members upon inhibition of glucose metabolism. Among the antiapoptotic members of the Bcl-2 family, Mcl-1 is of particular interest because (1) it contains a G þ C rich (>70%) 5 0 untranslated region (Mills et al, 2008) and (ii) given that Mcl-1 protein is highly regulated and rapidly degraded (Zhong et al, 2005;Maurer et al, 2006), inhibition of its synthesis would lead to a major decrease in protein level. Finally, several lines of evidence are in support of Mcl-1 regulation at the translational level.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several lines of evidence are in support of Mcl-1 regulation at the translational level. Studies have suggested that, in other contexts, Mcl-1 is a potential downstream target of eIF4E (Wei et al, 2006;Wendel et al, 2007;Mills et al, 2008). Recently Wei et al (2006) described the ability of rapamycin (mTOR inhibitor) to induce Mcl-1 but not Bcl-2 or Bcl-XL block in protein translation.…”
Section: Discussionmentioning
confidence: 99%